OPTIMALISASI PERAN KEPALA DESA DALAM PEMBANGUNAN JARINGAN INTERNET LOKAL MELALUI RPJMDes (Studi Desa Tambakrejo Kecamatan Waru Kabupaten Sidoarjo) - Ramadhan, Mochammad Fahri Ilmi; Eprilianto, Deby Febriyan (Universitas Negeri Surabaya, 2024)
Rural development, especially infrastructure, opens opportunities for community institutions to develop according to social and cultural needs and conditions. This study aims to explore the role of the village head in the development of local internet network infrastructure in Tambakrejo Village, Waru District, Sidoarjo Regency. The method used is descriptive with a qualitative approach, through interviews, observations, and documentation. The focus of the study is the leadership role theory according to Bintoro Tjokroamidjojo. The analysis shows that the role of the village head is not yet optimal. As a motivator, interpersonal communication has been established, but the initiative to gather community aspirations is still lacking, relying on formal events such as RT/RW meetings and Musrenbangdesa (Village Development Planning Meetings). As a facilitator, the village head has not provided adequate administrative infrastructure and lacks supervision over development. However, as a mobilizer, the village head is quite good at socializing and involving the community in the Village Government Work Plan (RKP). This research is expected to enhance the understanding of regional government administration, particularly in the development of Public Administration studies.